Examining the Impact of the Book of Enoch, Sefer Yetzirah, and Greek Civilization on the Jewish Calendar System: An Islamic Astronomical Law Perspective - Azkarrula, Youla Afifah; Hoffmann, Susanne M.; Izzuddin, Ahmad (Institut Agama Islam Negeri (IAIN) Pontianak, 2023)
This article analyzes changes in the reference system of the Jewish Calendar. Initially, the Jewish Calendar reference was based on the movement of the Sun. However, the calendar system used by the Jewish community worldwide now refers to two celestial objects, the Sun and the Moon. This study is literature research with a qualitative approach and uses the Book of Enoch and the Sefer Yetzirah as primary sources. The authors found that the first reference system of the Jewish Calendar, which was based on the movement of the Sun (Solar), follows the description in the Book of Enoch and the Sefer Yetzirah. These two books explain the calendar system used by Prophet Idris to Prophet Moses. The Solar Calendar reference system was later replaced with the Lunar Calendar in the second century BCE. Six centuries later, the Jewish Calendar returned to using a Solar Calendar combined with the Lunar Calendar, known as the Lunisolar Calendar. The latest reference system is a mathematical calendar with the Metonic cycle that refers to the movement of the Sun and Moon. The authors argue that the influence of the Greek civilization and the adjustment of the difference between the Lunar and Solar Year caused the changes in the reference system of the Jewish Calendar.